Horizontal Gene Transfer Clarifies Taxonomic Confusion and Promotes the Genetic Diversity and Pathogenicity of Plesiomonas shigelloides - Zhiqiu Yin (American Society for Microbiology, 2020)
ABSTRACT Plesiomonas shigelloides is an emerging pathogen that has been shown to be involved in gastrointestinal diseases and extraintestinal infections in humans. However, the taxonomic position, evolutionary dynamics, and pathogenesis of P. shigelloides remain unclear. We reported the draft genome sequences of 12 P. shigelloides strains representing different serogroups. We were able to determine a clear distinction between P. shigelloides and other members of Enterobacterales via core genome phylogeny, Neighbor-Net network, and average genome identity analysis. The pan-genome analysis of P. shigelloides revealed extensive genetic diversity and presented large flexible gene repertoires, while the core genome phylogeny exhibited a low level of clonality. The discordance between the core genome phylogeny and the pan-genome phylogeny indicated that flexible accessory genomes account for an important proportion of the evolution of P. shigelloides, which was subsequently characterized by determinations of hundreds of horizontally transferred genes (horizontal genes), massive gene expansions and contractions, and diverse mobile genetic elements (MGEs). The apparently high levels of horizontal gene transfer (HGT) in P. shigelloides were conferred from bacteria with novel properties from other taxa (mainly Vibrionaceae and Aeromonadaceae), which caused the historical taxonomic confusion and shaped the virulence gene pools. Furthermore, P. shigelloides genomes contain many macromolecular secretion system genes, virulence factor genes, and resistance genes, indicating its potential to cause intestinal and invasive infections. Collectively, our work provides insights into the phylogenetic position, evolutionary dynamic, and pathogenesis of P. shigelloides at the genomic level, which could facilitate the observation and research of this important pathogen. IMPORTANCE The taxonomic position of P. shigelloides has been the subject of debate for a long time, and until now, the evolutionary dynamics and pathogenesis of P. shigelloides were unclear. In this study, pan-genome analysis indicated extensive genetic diversity and the presence of large and variable gene repertoires. Our results revealed that horizontal gene transfer was the focal driving force for the genetic diversity of the P. shigelloides pan-genome and might have contributed to the emergence of novel properties. Vibrionaceae and Aeromonadaceae were found to be the predominant donor taxa for horizontal genes, which might have caused the taxonomic confusion historically. Comparative genomic analysis revealed the potential of P. shigelloides to cause intestinal and invasive diseases. Our results could advance the understanding of the evolution and pathogenesis of P. shigelloides, particularly in elucidating the role of horizontal gene transfer and investigating virulence-related elements.